Pre-treatment Neutrophil-to-Lymphocyte Ratio significantly affects progression free survival in positive EGFR mutation advanced lung adenocarcinoma with EGFR-TKI treatment in Bali, Indonesia - Widiasari Ni Putu Ayu; Rai Ida Bagus Ngurah; Dwi Kusumawardani Ida Ayu Jasminarti; Sajinadiyasa I Gede Ketut; Candrawati Ni Wayan; Arisanti Ni Luh Putu Eka (Sciendo, 2023)
Introduction: Today, recommendations about initial Response Evaluation Criteria in Solid Tumor (RECIST) and its frequency still vary, while early diagnosis of progression affects patient's prognosis and subsequent treatment options.